IMPACT OF INFORMATION TECHNOLOGY AND MACHINE LEARNING ON DIGITAL TEACHING, LEARNING, AND HRM - Aworou, M. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The emergence of new and advanced technologies has sparked rapid transformations in various spheres of life, particularly in the realm of education. The growing utilization of machine learning and information technology in educational settings is disrupting traditional teaching and learning methods. This article offers a comprehensive exploration of the influence of machine learning and information technology on digital education, learning methodologies, and human resource management within the educational sector. As technology continues to permeate everyday life, it profoundly affects all areas of the curriculum. The widespread availability of global communication through technology enables immediate access to copious amounts of information, thereby challenging learners' assimilation and evaluation abilities. With increasing accessibility of IT at home, work, and educational institutions, learning becomes an ongoing pursuit that necessitates continual assessment of the learning process itself. This paper delves into the obstacles and prospects arising from the integration of information technology in education, while also presenting insights into leveraging this transformative process for enhanced efficacy in teaching, learning, and HR management.